STRATEGI MEMENANGKAN PERSAINGAN DENGAN BALANCED SCORECARD - Nuryati, Siti (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2009)
Abstract:Balanced scorecard is a management step, which is needed to improve the organization's financial performance in the process. Measurement of non-financial and financial information systems part of all staff throughout the organization. Balanced scorecard as a tool to exchange the work process, which must be with some organization that recently envisioned. Some companies which are designed on a vision and strategy can not be controlled for the competitive position in BSC. Companies can propaganda on planning to make an appointment BSC can also provide measurement system better. In the competitive process is prepared BSC consists of the implementation of interviews, workshops, and estimates on a reconsideration of research each year. As part of strategic planning is the location of the main objectives, therefore, can perform the primary purpose strategy location is therefore better able to perform the BSC to give effect to the level of customer satisfaction and improve the level of achievement. Customers will be loyal to the company if the company agreed to complete the request in a timely mannerKeyword:balance score value, financial performance